Evaluasi Kebijakan Pembangunan Wisata Religi di Kabupaten Gresik (Studi Wisata Makam Sunan Giri dan Situs Giri Kedaton) - Yusuf Hariyoko; Adi Soesiantoro; Revi Pravira Pangestuti (Publica: Jurnal Pemikiran Administrasi Negara, 2021)
The tourism sector provides positive benefits for growing the community's economic sector if it is managed properly. Gresik Regency already has the Gresik Regency Regional Tourism Development Master Plan 2013-2025 as the basis for developing the tourism sector. This research uses descriptive qualitative research type. Data collection data in research using interview techniques, observation, and documentation. To evaluate or assess the success of this religious tourism development policy using several theories from Stufflebeam: context evaluation, input evaluation, process evaluation, product evaluation. The results of this study notes that the success of religious tourism development policies in Gresik Regency, especially in the Sunan Giri Tomb and Giri Kedaton Site has not been fully successful optimally because of differences in visits and tourism interests between the Sunan Giri Tomband Kedaton Giri Site due to the lack of promotion of Giri Site tourism Kedaton. One solution that can be recommended by researchers at the Gresik Regency's Office of Tourism and Culture is to increase efforts to promote the Giri Kedaton Site as an attractive destination in Gresik Regency